2019
DOI: 10.3389/fcimb.2019.00256
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Its Role on Viral Evasion: Is It With Us or Against Us?

Abstract: Viruses are obligate intracellular pathogens that require the protein synthesis machinery of the host cells to replicate. These microorganisms have evolved mechanisms to avoid detection from the host immune innate and adaptive response, which are known as viral evasion mechanisms. Viruses enter the host through skin and mucosal surfaces that happen to be colonized by communities of thousands of microorganisms collectively known as the commensal microbiota, where bacteria have a role in the modulation of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 66 publications
1
73
0
1
Order By: Relevance
“…Additionally, fecal transplantation was approved for clinical trials as a therapeutic option for SARS-CoV-2-related pneumonia based on the promising results obtained from fecal microbiota transplantation in patients suffering from antibiotic-associated diarrhea, active ulcerative colitis, and other viral infections [103][104][105][106]. Recently, it was found that intestinal microbiota-derived IFN in lung stroma confers protection against viral diseases such as avian influenza and respiratory syncytial virus [103].…”
Section: Control and Treatment Of Covid-19 Infectionmentioning
confidence: 99%
“…Additionally, fecal transplantation was approved for clinical trials as a therapeutic option for SARS-CoV-2-related pneumonia based on the promising results obtained from fecal microbiota transplantation in patients suffering from antibiotic-associated diarrhea, active ulcerative colitis, and other viral infections [103][104][105][106]. Recently, it was found that intestinal microbiota-derived IFN in lung stroma confers protection against viral diseases such as avian influenza and respiratory syncytial virus [103].…”
Section: Control and Treatment Of Covid-19 Infectionmentioning
confidence: 99%
“…It is well-known that the commensal bacteria in the GI tract impact the immune response. Some possible mechanisms involve microbiota affecting and regulating cytokine production ( 103 ), while others involve microbiota modulation of the production of mucous and antiviral defensins and ROS ( 104 ). In regard to viral infections, however, some microbiota elicit protective effects, while others serve as a route of viral entry and infection.…”
Section: Immune Responsementioning
confidence: 99%
“…The mechanism underlying the interactions between the lung microbiota and viruses are currently not fully understood. It is known that the lung resident microbiota modulates viral infections yielding beneficial outcomes, conferring protection against viral infection, or harmful outcomes since virus can use the resident bacteria to spread in the host by direct or indirect mechanisms [30,31,32,33]. Moreover, viruses can perturb the integrity of the commensal microbiota (modified by viral infections, age, and smoke), that in turn influences virus infectivity and morbidity [31].…”
Section: Figurementioning
confidence: 99%